Quality of Life After Pancreaticoduodenectomy Using Different Reconstruction Techniques: A Follow-up Multicenter Study - Pezzilli, Raffaele; Falconi, Massimo; Zerbi, Alessandro; Casadei, Riccardo; Morselli-Labate, Antonio Maria (JOP. Journal of the Pancreas, 2012)
Context The only available data on quality of life (QoL) in different types of reconstruction techniques for pancreatic head resection (PHR) come from randomized studies and these studies compare only two approaches such as pancreaticojejunostomy (PJ) and pancreaticogastrostomy (PG). We have no available QoL data on unselected patients as happens in routine clinical practice; in fact, surgeons tend to prefer one technique over the various other possibilities. Objective To evaluate the QoL in a 2-year follow-up study in consecutive subjects who underwent PHR with different reconstruction techniques (PJ layer end-to-side PJ (LEPJ) or duct-to-mucosa PJ (DMPJ)) with or without trans-anastomotic pancreatic duct stenting (TASPJ)] or PG. Patients One-hundred and 97 consecutive patients enrolled in three Italian surgical centres were studied: 164 (83.2%) had malignant and 33 (16.8%) had benign disease. Methods The EORTC QLQ-C30 questionnaire was administered at 5 different times for evaluation: before surgery and 6, 12, 18 and 24 months after discharge. Results PJ was performed in 189 patients (95.9%) (LEPJ in 124 (65.6%), DMPJ in 65 (34.4%)); 18 out of the 65 DMPJ patients (27.7%) had a TASPJ. A PG was carried out in 8 patients (4.1%) only. In the follow-up evaluation, the QoL significantly improved using the various surgical approaches; improvement over time was not significantly different between the PJ and the PG patients as well as between DMPJ and LEPJ, or between those with and without TASPJ. Conclusions In clinical practice surgeons should use a reconstruction technique in which they are experts; this is supported by the fact that the different surgical reconstruction techniques are equally effective in improving the QoL after PHR.